Analisis Peran Micro Influencer Dalam Meningkatkan Brand Awareness Produk Skintific - Teuku Muhammad Win Dafri Darisa; Daneswara Jayalaksana; Ridwan Roy Tutupoho; Erwin Permana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Beauty products have become a promising business, especially after the COVID-19 pandemic. Various brands have achieved high sales figures, one of which is Skintific products. This study aims to analyze the role of micro-influencers in increasing brand awareness of Skintific products. The study was conducted using a descriptive qualitative approach. Research data was obtained from literature reviews, digital observations, and official publications related to the topic. The results of the study indicate that micro-influencers play a significant role in increasing brand awareness for Skintific products. With a higher engagement rate compared to macro-influencers, micro-influencers are able to build closer and more authentic relationships with their audience, making their recommendations more trustworthy than conventional advertisements. Despite having a smaller number of followers, micro-influencers demonstrate greater effectiveness in creating engaging content such as product reviews, tutorials, and unboxing videos, which increase consumer interest and trust in the product. Research data shows that micro-influencers' engagement rate (5.07%) is higher than that of macro-influencers (3.25%), despite their more limited reach. The success of this marketing strategy is also supported by the use of social media platforms such as Instagram and TikTok, which enable the distribution of interactive visual content and expand brand awareness organically. With increased audience engagement, Skintific has not only succeeded in strengthening brand awareness but also in building product credibility, which ultimately contributes to increased consumer interest and purchasing decisions.